Corporate governance reforms and shareholders’ confidence in emerging markets - Rahman, Haseeb-Ur (Emerald Publishing Limited, 2017)
Purpose – The purpose of this paper is to investigate the relation of corporate governance (CG) attributes, such as separate leadership (SL) structure, independent chair (IC) of the board, and the proportion of independent directors on the board (Bind) recommended by the new Malaysian Code on Corporate Governance (2012), with firms’ market performance measured by share market price. Design/methodology/approach – The paper uses a randomly selected sample of 150 non-financial Malaysian listed companies.To find the distinct impact of the code, the paper explicitly divides the sample into two-year pre-context (2010-2011) and two-year post-context (2013-2014) of the code. Besides descriptive statistics, the study also employs correlation and multiple regression estimators. Findings – By comparing the pre-context and post-context of the code, the study found that SL and Bind have a significant positive relation while IC of the board has a significant negative relation with share market price after enactment of the code.Research limitations/implications – The paper has a limitation of using only two years of data due to its non-availability particularly after enactment of the code.The findings show that the new code slightly improved compliance to the CG attributes investigated.Based on findings, the study also recommends further improvement in compliance to CG codes and other voluntary regulations in Malaysia. Originality/value – Besides contributing to the limited and incongruent literature in pre-context and postcontext of CG regulations, the paper also provides important insights for regulators and policy makers of the emerging markets like Malaysia.